Effectiveness of CBNAAT in the diagnosis of extrapulmonary tuberculosis - Kasat, Shivprasad; Biradar, Mahendra; Deshmukh, Ashish; Jadhav, Sunil; Deshmukh, Hafiz (International Journal of Research in Medical Sciences, 2018)
Background: Tuberculosis is still a major health problem worldwide. It is estimated that about one-third of the world’s population is infected with mycobacterium tuberculosis. Whilepulmonary tuberculosis is most common presentation; extrapulmonary tuberculosis is also an important clinical problem. CBNAAT is cartridge based nucleic acid amplification test with a well-established role in the diagnosis of pulmonary tuberculosis (PTB). We determined the effectiveness of CBNAAT in the diagnosis of extrapulmonary tuberculosis (EPTB) cases in comparison to AFB smear. Methods: Retrospective study of suspected extrapulmonary tuberculosis patients in a tertiary care centre of the study area was conducted. The study period was from January 2017 to July 2018. Data of 166 consecutive suspected extrapulmonary tuberculosis patients was retrieved. Effectiveness of CBNAAT in the diagnosis of EPTB was assessed as compared to that of AFB smear. Results: Samples collected from 166 suspected EPTB patients were subjected to AFB smear and CBNAAT. Samples collected included lymph node, pus, pleural fluid, tissue, CSF, gastric lavage, cystic fluid, peritoneal fluid, ascitic fluid, colonic fluid, synovial fluid, urine. In AFB smear results, 17 cases were positive for TB bacilli and 149 were negative for the same. In CBNAAT results, 25 cases were positive for TB bacilli and 141 cases were negative. In comparative analysis, 8 cases were AFB smear negative but CBNAAT positive. Conclusions: CBNAAT is a useful tool in the diagnosis of EPTB cases because of its simplicity and rapid turnaround time. CBNAAT is more effective as compared to AFB smear in the diagnosis of EPTB cases.